Characteristics of Vibrating Composite Stiffened Hypars with Cut-Out at Different Modes - SAHOO, Sarmila (Engineering Transactions, 2019)
Vibration characteristics of laminated composite stiffened hypar (hyperbolic paraboloid shell bounded by straight edges) with cut-out are analysed in terms of natural frequency and mode shapes. A finite element code is developed for the purpose by combining an eight noded curved shell element with a three noded curved beam element for stiffener. Finite element formulation is based on first order shear deformation theory and includes the effect of cross curvature. The isoparametric shell element used in the present model consists of eight nodes with five degrees of freedom per node while beam element has four degrees of freedom per node. The code is validated by solving benchmark problems available in the literature and comparing the results. The generalised Eigen value solution is chosen for the un-damped free vibration analysis. New results are presented for first five modes of natural frequency by varying boundary conditions, ply orientation and curvature of the shell. The results furnished here may be readily used by practicing engineers dealing with stiffened composite hypars with cut-outs.